Деградационные превращения в топологически разупорядоченных твердых телах: 4. Особенности экспоненциальной кинетики - Balitskaya, V. A.; Brunets, I. M.; Vakiv, М. M.; Klim, G. I.; Shpotyuk, O. I. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The manifestations of exponential degradation kinetics in topologically disordered materials are analyzed. Degradation transformations are determined by a single prevailing activation energy value, regardless of the structural dispersity of the system. Non-exponential degradation kinetics correspond to either stretched or compressed relaxation functions. Stretched kinetics are characteristic of intrinsic degradation transformations in systems homogeneous by nature. Transformations involving two or more elementary processes are described by compressed kinetics.